Diurnal variation in forced vital capacity in patients with fibrotic interstitial lung disease using home spirometry. Issue 1 (6th April 2020) - Moor, Catharina C.; van den Berg, Carlijn A.L.; Visser, Lidewij S.; Aerts, Joachim G.J.V.; Cottin, Vincent; Wijsenbeek, Marlies S.
Forced vital capacity (FVC) is used as the routine physiological measure to assess disease progression in fibrotic interstitial lung diseases (f-ILDs) [1]. New drugs are currently being investigated on top of "standard care" with antifibrotic drugs in idiopathic pulmonary fibrosis (IPF) and other f-ILD, resulting in small margins of change in FVC [2, 3]. Recently, the first trial of antifibrotic medication in patients with systemic sclerosis-associated interstitial lung disease has shown a numerically small but significant lower annualised rate of FVC decline (41 mL) in patients treated with nintedanib compared with placebo [3]. This study demonstrates a diurnal variation in FVC measured with home spirometry in patients with f-ILD, with a higher FVC in the morning than in the afternoon http://bit.ly/37SQtBK